Influence of biochar and nitrogen on fine root morphology, physiology, and chemistry of Acer mono - Muhammad Razaq (Nature Portfolio, 2017)
Abstract Fine roots play an important role in the overall functions of individual plants. Previous studies showed that fertilization and available soil resources have a notably profound effect on fine root, but there is lack of study centered on how fine root morphology, physiology, and chemistry respond to biochar with N additions. Different levels of biochar (0, 10, 15, and 20 g) and N (0, 2, 4 and 6 g) were applied to Acer mono seedling plants in a field nursery. The root system morphology and root chemistry and physiology were evaluated in line with root length, root diameter, SRL, N and N: C and root respiration. Biochar and N significantly affected root morphology, chemistry and root respiration. Morphological, chemical and physiological parameters were found to be at their maximum with 20 g biochar and 6 g N; however, no significant effect was noted on fourth- and fifth-order roots. Furthermore, a significant increase in root respiration was recognized with the increase in root tissue N concentration and the negative relationship of root respiration with higher branch order. Thus, overall, study parameters indicate that biochar and nitrogen positively influence the Acer mono fine root, and therefore should be used to improve fine root health.